Perancangan Sistem Informasi Jasa Cuci Mobil dan Motor Doorsmeer - Syafrinal; Bahruni (Journal Innovations Computer Science, 2022)
The purpose of the research is to design an information system for car and motorcycle washing services that will be used by doormeer business users, which is expected to assist doormeer entrepreneurs in recording every transaction, queue, payroll management and can be used with various platforms both desktop and mobile. In the process of designing an information system for doormeer car and motorcycle washing services, we use the DevOps software design method. From the results of research and observations that have been made on Doorsmeer CV. XYZ, it can be concluded that from the results of the design of an information system for car and motorcycle washing services at Doorsmeer CV. XYZ web-based parties make it easy to inform washing services that are ready to use through the ordering system. With the website, customers can access and get information and order services quickly from their homes, and can choose the services they want to use according to the customer's plan, and Applications information system for car and motorcycle washing services at Doorsmeer CV. XYZ can handle and control and supervise service transaction data, create invoices that can avoid delays and in making contract reports for each transaction activity.